1985
DOI: 10.1111/j.1748-7692.1985.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Biophysics of Marine Mammals

Abstract: The underwater existence of marine mammals has encouraged a variety of special biophysical adaptations to their environment. Their sensory and communication systems reflect the transmission properties of sea water. For example, vision is keen in spectra that penetrate water best, vocalization is broadband and used at the frequencies that appear to fit their activities best—the differences in sensory use match the intriguing variety of behavior observed for each species. To date most of the observations of anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(67 citation statements)
references
References 156 publications
0
66
0
1
Order By: Relevance
“…In addition, the bias of training must be accounted for as much as possible since psychophysical methods are principally used to determine animal sensory thresholds. This was clearly demonstrated by Watkins and Wartzok (1985).…”
Section: Abstract (Maximum 200 Worah)mentioning
confidence: 58%
See 1 more Smart Citation
“…In addition, the bias of training must be accounted for as much as possible since psychophysical methods are principally used to determine animal sensory thresholds. This was clearly demonstrated by Watkins and Wartzok (1985).…”
Section: Abstract (Maximum 200 Worah)mentioning
confidence: 58%
“…Each pool was monitored on separate channels with independent hydrophones. Cetaceans are capable of using a wide variety of sounds depending upon the task being performed (Watkins and Wartzok, 1985). Au et al (1974) has suggested that bottlenose dolphins change their signals to compensate for differences in ambient noise levels.…”
Section: Abstract (Maximum 200 Worah)mentioning
confidence: 99%
“…Similarly, bottlenose dolphins (Tursiops truncatus) produce frequencymodulated whistles that are sufficiently distinctive that human listeners can learn to distinguish the whistles of individual dolphins by ear . These individually distinctive whistles, called signature whistles, may comprise over 90% of the whistles produced by an individual Sounds are of obvious importance to most marine mammals, and most appear to use purposefully-produced sound underwater (Watkins and Wartzok 1985). Sound…”
Section: Analysis Of Undecided Interactionsmentioning
confidence: 99%
“…Visual, chemical, electrical, and tactile signals are undoubtedly important for many marine species, but they are best suited to communication over relatively short distances (Watkins .and Wartzok 1985).…”
Section: Analysis Of Undecided Interactionsmentioning
confidence: 99%
“…This belief is mainly based on an interpretation of neuroanatomical and genetic evidence, such as a reduced size of the olfactory bulbs and a low number of functional olfactory genes (Fobes & Smock 1981, Reep et al 2007. However, the fact that both peripheral and central olfactory structures exist in pinnipeds challenges this assumption of poor olfactory capacity (Kuzin & Sobolevsky 1976, cited by Lowell & Flanigan 1980, Watkins & Wartzock 1985. Furthermore, an increasing number of behavioral studies suggest that pinnipeds may use their sense of smell in a variety of behavioral contexts including social communication, foraging, food selection, and reproduction.…”
Section: Introductionmentioning
confidence: 99%